Urinary biomarkers of oxidative stress and plasmatic inflammatory profile in phenylketonuric treated patients. Issue 47 (8th October 2015) - Deon, Marion; Sitta, Angela; Faverzani, Jessica L.; Guerreiro, Gillian B.; Donida, Bruna; Marchetti, Desirèe P.; Mescka, Caroline P.; Ribas, Graziela S.; Coitinho, Adriana S.; Wajner, Moacir; Vargas, Carmen R.
Abstract: Oxidative stress has been proposed as an important pathophysiologic feature of various inborn errors of metabolism, including phenylketonuria (PKU). Considering that there are few studies relating oxidative stress and inflammation directly in PKU disease, the aim of this study was to evaluate and correlate oxidative damage to biomolecules, antioxidant defenses, pro‐inflammatory cytokines, phenylalanine (Phe) and its metabolites (phenyllactic acid—PLA and phenylacetic acid—PAA) levels in urine and plasma from patients with PKU under dietary treatment. We observed a marked increase of isoprostanes, which is a lipid peroxidation biomarker, in urine from these treated patients. Next, we demonstrated that protein oxidative damage, measured by di‐tyrosine formation, was significantly increased in urine from PKU treated patients and that decreased urinary antioxidant capacity was also observed. Our findings concerning to the inflammatory cytokines interleukin‐6 and interleukin‐1β, both significantly increased in these patients, provide evidence that the pro‐inflammatory state occurs. Besides, interleukin‐1β was positively correlated with isoprostanes. We observed a negative correlation between interleukin‐6 and interleukin‐10, an anti‐inflammatory cytokine. Di‐tyrosine was positively correlated with Phe, which indicates oxidative damage to proteins, as well as with PAA. These findings may suggest that the protein damage may be induced by Phe and its metabolite PAA in PKU. Our results indicate that pro‐oxidant and pro‐inflammatory states occur and are, in part, correlated and protein oxidation seems to be induced by Phe and PPA in PKU patients.